Functions of Redox Signaling in Pollen Development and Stress Response - Dong-Ling Xie; Xue-Lian Zheng; Can-Yu Zhou; Mukesh Kumar Kanwar; Jie Zhou (MDPI AG, 2022)
Cellular redox homeostasis is crucial for normal plant growth and development. Each developmental stage of plants has a specific redox mode and is maintained by various environmental cues, oxidants, and antioxidants. Reactive oxygen species (ROS) and reactive nitrogen species are the chief oxidants in plant cells and participate in cell signal transduction and redox balance. The production and removal of oxidants are in a dynamic balance, which is necessary for plant growth. Especially during reproductive development, pollen development depends on ROS-mediated tapetal programmed cell death to provide nutrients and other essential substances. The deviation of the redox state in any period will lead to microspore abortion and pollen sterility. Meanwhile, pollens are highly sensitive to environmental stress, in particular to cell oxidative burst due to its peculiar structure and function. In this regard, plants have evolved a series of complex mechanisms to deal with redox imbalance and oxidative stress damage. This review summarizes the functions of the main redox components in different stages of pollen development, and highlights various redox protection mechanisms of pollen in response to environmental stimuli. In continuation, we also discuss the potential applications of plant growth regulators and antioxidants for improving pollen vigor and fertility in sustaining better agriculture practices.